2007
DOI: 10.1007/s10517-007-0215-7
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic activity of n-tyrosol during acute myocardial ischemia and reperfusion

Abstract: Antiarrhythmic activity of n-tyrosol was demonstrated on the model of early occlusion and reperfusion arrhythmia. The preparation reduces the incidence of ventricular tachycardia and fibrillation, increases the percent of animals without ventricular arrhythmia, and moderates the severity of developing ventricular arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Plotnikov et al reported that intra-gastric p -tyrosol treatment in male Wistar rats led to a pronounced reduction in platelet aggregation and blood viscosity in these rats [14]. Additionally, it has been shown that the intravenous administration of p -tyrosol 10 min prior to coronary occlusion in an in vivo acute myocardial ischemia model of Wistar rats significantly reduced the arrhythmic activity occurring during myocardial ischemia and reperfusion [15]. Moreover, p -tyrosol induced myocardial protection against ischemia-induced stress, thereby prompting the development of a new drug to combat ischemic heart diseases (IHD) while revealing potential therapeutic molecular targets such as FOXO3a and SIRT1 that can be modulated to precondition the heart to overcome ischemic stress and to inhibit the activity of leukocyte 5-lipoxygenase [16].…”
Section: Introductionmentioning
confidence: 99%
“…Plotnikov et al reported that intra-gastric p -tyrosol treatment in male Wistar rats led to a pronounced reduction in platelet aggregation and blood viscosity in these rats [14]. Additionally, it has been shown that the intravenous administration of p -tyrosol 10 min prior to coronary occlusion in an in vivo acute myocardial ischemia model of Wistar rats significantly reduced the arrhythmic activity occurring during myocardial ischemia and reperfusion [15]. Moreover, p -tyrosol induced myocardial protection against ischemia-induced stress, thereby prompting the development of a new drug to combat ischemic heart diseases (IHD) while revealing potential therapeutic molecular targets such as FOXO3a and SIRT1 that can be modulated to precondition the heart to overcome ischemic stress and to inhibit the activity of leukocyte 5-lipoxygenase [16].…”
Section: Introductionmentioning
confidence: 99%
“…Tyrosol has been also effective in inhibiting leukocyte 5-lipooxygenase [6] and protecting the Caco-2 intestinal mucosa cells against the cytostatic and cytotoxic effects produced by oxidized LDL [7]. Many other activities of tyrosol were described such as its ability to inhibit ADP-induced platelet aggregation [8], to significantly reduce the arrhythmic activity that occurs during myocardial ischemia and reperfusion [9], and to possess significant neuroprotective activities against glutamate-induced neurotoxicity in primary cultures of rat cortical cells and injury induced by 5-S-cysteinyl-dopamine in vitro [10]. Hence, lipophilic derivatives of tyrosol and, in particular, esters bearing acyl chains, exhibit a better affinity with lipophilic membrane constituents.…”
Section: Introductionmentioning
confidence: 99%
“…Plotnikov et al, have shown that intra-gastric n-tyrosol treatment in male Wistar rats exhibited pronounced reduction in platelet aggregation and blood viscosity in these rats (21). It was also shown that intravenous administration of n-tyrosol 10 min prior to coronary occlusion in in vivo acute myocardial ischemia model of Wistar rats, significantly reduced the arrhythmic activity that occurs during myocardial ischemia and reperfusion (22). Hydroxy-tyrosol treatment of HepG2 cells, improved the antioxidant defense system of these cells while increasing cellular integrity and stress resistance capabilities (23).…”
Section: Introductionmentioning
confidence: 99%